2020
DOI: 10.5194/aab-63-1-2020
|View full text |Cite
|
Sign up to set email alerts
|

Research of postpartum endometritis in Japanese Black cattle with cystic ovarian disease by vaginal mucus test and endometrial cytology

Abstract: The relationship between endometritis and cystic ovarian disease (COD) is still unclear in Japanese Black cattle. Endometritis is classified into clinical endometritis (CE) and subclinical endometritis (SE). The objective of this study was to clarify the interaction between postpartum endometritis (CE and SE) and COD in Japanese Black cattle. Twenty-six suckled cows with COD (COD group) and 16 suckled cows with cyclical ovarian activity (CA group) were submitted for the experiment. Uterine conditions of cows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, current investigations have also confirmed an interaction existing between endometritis and cystic ovarian disease (COD) in Japanese black cattle [90]. According to the authors of the study, COD also has potential effects for endometritis, beside E. coli at 40-60 DPP, compared with cows with a normal ovarian cycle [90]. Similarly, a research report by Mohammed and colleagues [91] further demonstrated that endometritis has a significant adverse effect on the postpartum ovarian cycle of Holstein dairy cows.…”
Section: Clinical and Sub-clinical Endometritismentioning
confidence: 56%
See 1 more Smart Citation
“…On the other hand, current investigations have also confirmed an interaction existing between endometritis and cystic ovarian disease (COD) in Japanese black cattle [90]. According to the authors of the study, COD also has potential effects for endometritis, beside E. coli at 40-60 DPP, compared with cows with a normal ovarian cycle [90]. Similarly, a research report by Mohammed and colleagues [91] further demonstrated that endometritis has a significant adverse effect on the postpartum ovarian cycle of Holstein dairy cows.…”
Section: Clinical and Sub-clinical Endometritismentioning
confidence: 56%
“…On the other hand, current investigations have also confirmed an interaction existing between endometritis and cystic ovarian disease (COD) in Japanese black cattle [90]. According to the authors of the study, COD also has potential effects for endometritis, beside E. coli at 40-60 DPP, compared with cows with a normal ovarian cycle [90].…”
Section: Clinical and Sub-clinical Endometritismentioning
confidence: 72%
“…Individual researchers have reported that the incidence of ovarian cysts in dairy cattle can range from 3-15 % (Cattaneo et al, 2014) to 6-30 % (Yamamoto et al, 2020), with a peak incidence between 14 and 40 days after calving. According to some data, up to 70 % of ovarian cysts occur between 16 and 50 days after calving, with the highest incidence occurring between 30 and 40 days postpartum (Yimer et al, 2018).…”
Section: Postpartum Complications In Cows Are Associated With Hormona...mentioning
confidence: 99%